PERMAINAN TRADISIONAL DAERAH SEBAGAI SARANA PENGUATAN KARAKTER SISWA SEKOLAH DASAR - Ma’sumah Ma’sumah; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Journal of Innovation Research and Knowledge, 2022)
Character education must be carried out from an early age as the initial foundation for children to act and behave following the norms and values ​​that exist in society. Character education is not a difficult thing to do, especially for children who are still in primary school. Many ways are used to instill character education from an early age, one of which is by using traditional games. Traditional games are one of Indonesia's cultural heritages that contain various values ​​of the nation's honorable character. However, teachers often find it hard to use traditional games at school. This study aims to examine the ways that teachers can use traditional games as a means of strengthening character, especially students in primary schools. The method used in this research is Literature Review. Literature sources in the form of articles obtained from the Google Scholar database in journals in Indonesia in 2018-2022. The results of this study are the ways teachers can use traditional games in strengthening character education, including 1) integration of traditional games in various lessons; 2) integration in extracurricular activities; 3) traditional games are played outside of study hours; 4) the use of traditional games for a competition at school. Characters that developed from traditional games are very diverse, depending on the type of game used.